PEMBINAAN KEBERAGAMAAN DAN KEILMUAN GENERASI MUDA DI MADRASAH DINIYAH ATTAQWA DESA CISONTROL KABUPATEN CIAMIS TAHUN 1983-1989 - Widiati Isana (Al-Tsaqafa : Jurnal Ilmiah Peradaban Islam, 2016)
This study aims at determining the profile of Madrasah Diniyah Attaqwa (MDA) in 1983-1989, the role of MDA in fostering religious and scientific spirit of young people in 1983-1989, and the pattern of fostering that has carried out in raising of religious and scientific spirit of young villagers in Cisontrol in 1983-1989. This research is started off the framework that Madrasah Diniyah as Islamic educational institutions must be able to do a planned and deliberate coaching and guiding in order to achieve integrated personality, the personality of Muslims, the totality of the physical, spiritual, and moral sense. This research uses the historical method. Type of data is qualitative and data collection techniques through interviews, documents, and literature. The results showed that the religious and scientific spirit of young villagers in Cisontrol Ciamis in 1983-1989 cannot be separated from the great role of MDA. The emergence of religious and scientific spirit is due to the fact that MDA’s profile is full of simplicity but keep a lot of achievements, the role of MDA gives spirit of strugle and uphold of Islamic teachings, as well as MDA’s fostering patterns give noticiable benefits